Contents in tumor-educated platelets as the novel biosource for cancer diagnostics - Zhang, Qianru; Song, Xianrang; Song, Xingguo (Frontiers in Oncology, 2023)
Liquid biopsy, a powerful non-invasive test, has been widely used in cancer diagnosis and treatment. Platelets, the second most abundant cells in peripheral blood, are becoming one of the richest sources of liquid biopsy with the capacity to systematically and locally respond to the presence of cancer and absorb and store circulating proteins and different types of nucleic acids, thus called “tumor-educated platelets (TEPs)”. The contents of TEPs are significantly and specifically altered, empowering them with the potential as cancer biomarkers. The current review focuses on the alternation of TEP content, including coding and non-coding RNA and proteins, and their role in cancer diagnostics.